2014
DOI: 10.1155/2014/902820
|View full text |Cite
|
Sign up to set email alerts
|

Amendment ofTephrosiaImproved Fallows with Inorganic Fertilizers Improves Soil Chemical Properties, N Uptake, and Maize Yield in Malawi

Abstract: Maize production in Malawi is limited mainly by low soil N and P. Improved fallows of N-fixing legumes such asTephrosiaandSesbaniaoffer options for improving soil fertility particularly N supply. The interactions ofTephrosiafallows and inorganic fertilizers on soil properties, N uptake, and maize yields were evaluated at Chitedze Research Station in Malawi. The results indicated that the level of organic matter and pH increased in all the treatments except for the control. Total N remained almost unchanged whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…For instance, Grzywacz et al [36] and Kamanula et al [38] found that the effectiveness of the pesticidal plant extracts could be attributed by the presence of bioactive chemical compounds in those plants. T. vogelii, which was found effective in reducing M. persicae population in the present study, has been reported previously to manage ticks, lice, and flies on livestock and crops in the fields [24,40], Plutella xylostella and Trichoplusia ni [6]. Belmain et al [41] discovered the presence of rotenone in T. vogelii, which should be accountable for the insecticidal efficacy against M. persicae on the B. oleracea field.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, Grzywacz et al [36] and Kamanula et al [38] found that the effectiveness of the pesticidal plant extracts could be attributed by the presence of bioactive chemical compounds in those plants. T. vogelii, which was found effective in reducing M. persicae population in the present study, has been reported previously to manage ticks, lice, and flies on livestock and crops in the fields [24,40], Plutella xylostella and Trichoplusia ni [6]. Belmain et al [41] discovered the presence of rotenone in T. vogelii, which should be accountable for the insecticidal efficacy against M. persicae on the B. oleracea field.…”
Section: Discussionsupporting
confidence: 68%
“…T. candida proved to be one of the most satisfactory green manures because it can flourish in poor soil for several years and has a dense foliage [ 103 ]. T. candida fallows alone can raise maize grain yield by 300% [ 104 ]. In South Rwanda, T. vogelii and Cajanus cajan were intercropped with Sorghum bicolor during the long rainy season.…”
Section: The Use Of Tephrosia Plants For Managimentioning
confidence: 99%
“…This raises the need for better awareness and education, but also highlights the importance of promoting lower risk pesticides such as pesticidal plant extracts. The lower risks of using plant extracts were explained by farmers, who reported that it was not necessary to take antidotes after spraying plant extracts to treat chest pain, an effect linked with effects acquired from spraying synthetic pesticides whereby drinking milk is often used as an antidote [38].…”
Section: Discussionmentioning
confidence: 99%